Percy Spann and Ethel Spann interviewed by Mark Schuster and Maria Zann in the Mark Schuster and Maria Zann folklore collection. - Spann, Percy; Spann, Ethel; Schuster, Mark.; Zann, Maria (1989)
Folkloric recording. Percy Spann and his wife, Ethel Spann, play a number of oldtime dance tunes on Hohner Club button accordion, piano and banjo-mandolin. Many of these tunes are unique to the Fassifern Valley region and were learnt from older musicians, including relatives. This interview contains tunes for old square dances (Lancers, First Set), a number of older German tunes, German songs and general talk about musicians, dances and history of the Fassifern district.
Recorded on 12 September 1989 in Rosevale, Queensland.
Digital master available
Summary not yet available.
Keywords: Spann, Percy -- Interviews; Spann, Ethel -- Interviews; German Australians -- Queensland -- Social life and customs; German Australians -- Queensland -- Music; Folk songs, German -- Queensland; Folk dance music -- Germany; Folk dance music -- Queensland